2011
DOI: 10.1177/1352458511431729
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of CSF oligoclonal banding in multiple sclerosis increases with latitude

Abstract: The results of this study indicate that latitude could explain some of the inconsistencies in OCB status reported in different populations. The study confirms that OCB positivity in MS is associated with a worse long-term prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 33 publications
(47 reference statements)
2
39
1
1
Order By: Relevance
“…Two of these studies specified ON,27 28 and one study specified a brainstem syndrome as the CIS 29. Twelve studies used conversion to clinically definitive multiple sclerosis (CDMS) as the outcome, one used radiological conversion to MS27 and one used the number of patients reaching EDSS 6 at 5 years 7. The study using EDSS 6 as the outcome measures was excluded given the very different outcome measure, leaving 13 studies in the analysis (see online supplementary appendix).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of these studies specified ON,27 28 and one study specified a brainstem syndrome as the CIS 29. Twelve studies used conversion to clinically definitive multiple sclerosis (CDMS) as the outcome, one used radiological conversion to MS27 and one used the number of patients reaching EDSS 6 at 5 years 7. The study using EDSS 6 as the outcome measures was excluded given the very different outcome measure, leaving 13 studies in the analysis (see online supplementary appendix).…”
Section: Resultsmentioning
confidence: 99%
“…There are a large number of studies examining this as either a primary or a secondary research question. The largest of these enrolled around 3000 patients 7. Although the advent of large MS databases has enabled population-based studies, there are limitations to using these, as different centres often use different techniques for detecting OCBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the latitudinal gradient of MS also affects clinical characteristics, although some recent studies11 12 have demonstrated a significant relationship between latitude and positivity for cerebrospinal fluid (CSF) oligoclonal bands (OCBs). A recent study in Japan has also confirmed this relationship between latitude and abnormal CSF findings, with a significant association of positive CSF findings (OR=4.08) and OCB positivity (OR=2.57) when comparing northern to southern Japan 13…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It is clear that the frequency of OB varies between countries and populations, and averages 80% globally. 10 One trivial reason for these differences is the quality of assays performed. However, other factors may also be in play.…”
Section: Diagnostic Valuementioning
confidence: 99%